SOME ASPECTS OF PREDICTING THE SEVERITY OF VIRUS-INDUCED BRONCHIAL ASTHMA EXACERBATION IN CHILDREN DUE TO COVID-19 PANDEMIC - Huzun , Dorin; Kostiv , Uliana; Sazhyn , Serhii; Sazhyna , Alla; Koliesnik , Dmytro (The Ukrainian Scientific Medical Youth Journal, 2021)
bronchial asthma is an important medical and social issue directly affects the health of patients, their quality of life, and the direct and indirect economic costs associated with the disease are quite significant. Due to the pandemic caused by a new strain of coronavirus SARS-CoV-2, international and domestic regulations documents have updated the management of patients with asthma. In particular, there have been recommendations for remote visits to assess the patients’ complaints however physical analysis and objective examination are not available during such consultations. It can lead to errors in diagnostic of asthma exacerbation severity and treatment tactic for prescription the reliever therapy. So it is actuality to find out additional indicators to improve the diagnostic and prediction of the severity of the disease exacerbations. Given the urgency of the problem, the aim of the study is to evaluate the clinical and paraclinical parameters in children with virus-induced bronchial asthma exacerbation to predict the severity of the asthma attack and personify the management of patients. Have been examined 47 patients who were hospitalized for disease exacerbation. The severity of a asthma attack was considered a group-forming feature. Statistical analysis was performed using parametric and nonparametric calculation methods, methods of clinical epidemiology and biostatistics. The results of the study give grounds to predict a more severe asthma attack among urban residents who have a phenotype of late-onset asthma. An additional, anamnestic risk of more severe exacerbation of the disease is body weight at birth, which exceeds 3500 g. Among spirometric indicators the highest prognostic criterion for severe bronchial asthma exacerbation was the general index of bronchodilation, which was 15% and above, as well as the index of bronchodilation at the level of the distal airways with a cut-off point of 30% and above. In the presence of the above risk factors for severe asthma attack on the background of confirmed infection with the coronavirus strain SARS-CoV-2 the patient needs hospitalization, antiviral treatment, increasing the dose of inhaled steroids and additional β2-agonists. When predicting a mild or moderate asthma attack provoked by the coronavirus SARS-CoV-2, it is advisable to continue remote monitoring by an allergist and the management of exacerbation includes a temporary increase daily dose of inhaled glucocorticosteroids and additional using of β2-agonists. It is recommended to avoid taking nebulizers and use individual metered powder or aerosol inhalers in cases of inpatient treatment.